Wildfire effects on the soil seed bank of a maritime pine stand: the importance of fire severity - Maia, P. (2019)
This study addressed the impacts of wildfire and, in particular, its severity on the seed bank of the litter/ash layer and the topsoil of a Mediterranean pine plantation (Pinus pinaster Ait.) in north-central Portugal. The study location was selected for presenting a homogeneous pine cover before the fire, on the one hand, and, on the other, heterogeneous patches with distinct degrees of damage to the pine crowns immediately after the fire. The experimental design involved the selection, from the opposite valley side, of three zones with adjacent strips of Low and High Canopy Consumption (L/HCC). Within each of these strips, a transect was laid out along which three plots were established at 10 m intervals. The same was done in the unburnt area immediately outside the fire perimeter. At each plot, samples were collected within the first two weeks after the fire to: (i) asses viable seed densities for three sampling layers, using the indirect method for a 10-month period; (ii) estimate maximum temperature reached (MTRs) at 0–3 cm depth, on the basis of Near Infrared Spectroscopy (NIR). Fire severity at the plots was further determined by verifying, in situ, pine canopy consumption (FCC) as well as by measuring the minimum diameter of remaining shrub twigs (TDI). In comparison with the unburnt area, the recently burnt area as a whole revealed a substantial increase in overall densities of viable seeds. Seed bank composition, however, varied markedly within the burnt area but this could be explained reasonably well by differential effects of the wildfire associated with its severity, in terms of the two crown consumption classes as well as the TDI index but not the MTRs. The inclusion of the litter/ash layer and the separation of two soil depths were amply justified by providing clear support for the important role of fire severity, in particular for the two principal taxa (Calluna vulgaris and Erica spp., presumably mainly E. australis).